Analisis Keterampilan Mengajar Mahasiswa Pendidikan Matematika pada Mata Kuliah Pembelajaran Matematika SMA - Lusia Bince Kumanireng (Journal on Education, 2024)
The purpose of this research is to determine the ability of prospective student educators in compiling learning tool components in the form of lesson plans, components of classroom learning implementation, personality and social components. The research method chosen in this study is a qualitative descriptive method with the data sources used being lesson plans prepared by students, learning videos carried out by practical students, and interviews to look at personality and social components. The research subjects were mathematics education students who were undertaking a teaching practice program. The results of the analysis show that the components of the Learning Implementation Plan (RPP) obtained an average score of ; The Learning Implementation Component Assessment obtained an average score of ; The personality and social component assessment obtained an average score of